أثر العلاقات الألمانية-الفرنسية في الاتحاد الأوربي وصنع قراره (1990-2009) - خليل محمد, نديم (Journal of College of Education, 2020)
The German-French axis is the basis for the start and decline of the European Union because of the common conviction of the importance of joint action within the European framework and the driving force for the development of the European Union and its completion of the components of polarity on its three economic, military and technological levels. Exercise influence within a broader regional circle, as German-French relations have always been measured by their shared ability to develop the EU, so they are described as engines of European integration, although there are such things as European construction. My military and financial resources cannot be based solely on their relations. Other European countries should be involved.The impact of German-French relations in the European Union was evident on many levels. Public relations in the European Union, and the impact of German-French relations in building an independent European military power